From Conservation to Regeneration: A Paradigm Shift in Seagrass-Ecotourism Management and Innovation Opportunities for Indonesia : Dari Konservasi ke Regenerasi: Pergeseran Paradigma dalam Pengelolaan Ekowisata Padang Lamun dan Peluang Inovasi bagi Indonesia - Jauhari, Muhammad Tantawi (Indonesian Journal of Tropical Biology, 2025)
Seagrass meadows are among the most productive coastal ecosystems, yet they are estimated to experience annual losses of approximately 7% due to ongoing conflicts between conservation objectives and local livelihood needs. This study maps the evolution of seagrass–ecotourism research from 2016 to 2025 and proposes a regenerative tourism framework tailored to the Indonesian context. A hybrid bibliometric analysis of 235 scientific publications was conducted, complemented by a Systematic Literature Review (SLR) of 27 key articles selected for relevance and methodological rigor. Knowledge structures and thematic clusters were visualized to identify dominant research trends and gaps. The results reveal a paradigm shift from ecology-centered studies toward integrated socio-economic and governance-oriented approaches. Indonesia contributes 41% of global research output, highlighting its role as a major seagrass hotspot and living laboratory for conservation-based tourism. Empirical evidence shows that integrating Regional Public Service Agency (BLUD) governance with Blue Carbon financing mechanisms, as observed in Raja Ampat, has strengthened financial support for seagrass conservation and restoration. Overall, the findings indicate a transition from passive conservation to regenerative management, where ecotourism serves as a strategic financing engine for ecosystem recovery. Integrating Indigenous and Local Knowledge (ILK) with carbon trading schemes is crucial to ensure long-term sustainability and resilience of seagrass ecosystems in the Anthropocene